The Welfare Of Cats - Rochlitz, Irene; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
This book, written by experts from the United Kingdom, the United States and Switzerland, presents up-to-date information on recent developments in our understanding of cat behavior, considers the ways in which cat welfare is assessed, and addresses the successes and failures of the relationship between cats and humans, including feline behavior disorders. It also deals with the ever-increasing problem of stray and unwanted cats in shelters, the feral cat population, and the effects of housing, disease, nutrition, and breeding on cat welfare. Although the focus is largely on cats in developed countries, this book should also be of relevance in developing countries, where issues affecting the welfare of domestic animals - not only of livestock but also of companion animals - are beginning to be identified and addressed. This volume will be of interest to all those concerned with the welfare of cats, including veterinarians, animal behaviorists, animal welfare organizations and cat owners.
Cat Behaviour: Social Organization, Communication And Development -- The Assessment Of Welfare -- The Human-Cat Relationship -- Behaviour Problems And Welfare -- Cat Overpopulation in the United States -- The Welfare Of Feral Cats -- Housing And Welfare -- Disease And Welfare -- Nutrition And Welfare -- Breeding And Welfare.
Keywords: LIFE SCIENCES; VETERINARY MEDICINE; ANIMAL BEHAVIOR; ZOOLOGY; ANIMAL GENETICS; ANIMAL PHYSIOLOGY; LIFE SCIENCES; ZOOLOGY; BEHAVIOURAL SCIENCES; VETERINARY MEDICINE; ANIMAL GENETICS AND GENOMICS; ANIMAL PHYSIOLOGY